Urban Agriculture in the Capital Area of Reykjavík - Ólafur Yngvi Stitelmann 1997- (2020)
This research is intended to provide an overview of current urban agriculture (UA) in the capital area and investigate the relationship between UA and sustainable urban development. This study is divided into a theoretical study of UA and a practical investigation of UA in the capital area. First, the social role of UA is looked at through the perspectives of personal and collective well-being, place-making and governance. Then, the economic and ecological functions of UA are investigated. Secondly, the case of UA in the capital area is studied more particularly. This investigation relies on interviews as well as an online survey. Results are assembled and then connected to the theoretical research in order to better depict the profile of UA in the capital area and determine its contribution to sustainable urban development.